1-Octyl-3-methylimidazolium hexafluorophosphate-functionalised magnetic poly β-cyclodextrin for magnetic solid-phase extraction ofpyrethroids from tea infusions. Issue 10 (3rd October 2021) - Xu, Qinqin; Liu, Zikai; Yan, Chen; Lu, Runhua; Zhou, Wenfeng
ABSTRACT: In this study, a novel sorbent, 1-octyl-3-methylimidazolium hexafluorophosphate functionalised magnetic poly β-cyclodextrin, was successfully synthesised and applied to magnetic solid-phase extraction for the determination of pyrethroids in tea infusions. The sorbent was characterised by transmission electron microscopy, energy-dispersive spectroscopy, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, vibrating sample magnetometer and Brunauer–Emmett–Teller measurement. All factors affecting extraction efficiency, such as sorbent amount, extraction time, ionic strength and desorption conditions, were optimised individually. Under the chosen conditions, wide linearity (2.5–500 μg L −1 ) with determination coefficients ranging from 0.9995 to 0.9999, low limits of detection of 0.32–0.54 μg L −1 and good precision (intra-day: 2.6–7.0%; inter-day: 3.5–7.6%) were achieved for four pyrethroids in tea infusions. The relative recoveries of target analytes in real tea infusion samples were from 70% to 101% with relative standard deviations lower than 9.1%. We conclude that the proposed method is promising in the detection of pyrethroids in tea infusions.